2012
DOI: 10.3810/psm.2012.11.1988
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Effectiveness of Different Exercise Programs for Patients with Osteoarthritis

Abstract: Exercise is recommended as a first-line conservative intervention approach for osteoarthritis (OA). A wide range of exercise programs are available, and scientific evidence is necessary for advising patients with OA on the optimal treatment strategy. The purpose of this review is to discuss the effectiveness of different types of exercise programs for OA based on trials, systematic reviews, and meta-analyses in the literature. Publications from January 1997 to July 2012 were searched in 4 electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 87 publications
3
54
0
7
Order By: Relevance
“…Improved pain control is associated with exercise for a variety of painful conditions 10 including chronic low back pain, 11,12 fibromyalgia, 13 osteoarthritis, 14 neuropathic pain, 15 and CRPS. 16 Various studies of healthy individuals have demonstrated a relationship between a person's participation in general physical activity and aerobic exercise and his or her tolerance to pain.…”
Section: How Does Exercise Affect Pain?mentioning
confidence: 99%
“…Improved pain control is associated with exercise for a variety of painful conditions 10 including chronic low back pain, 11,12 fibromyalgia, 13 osteoarthritis, 14 neuropathic pain, 15 and CRPS. 16 Various studies of healthy individuals have demonstrated a relationship between a person's participation in general physical activity and aerobic exercise and his or her tolerance to pain.…”
Section: How Does Exercise Affect Pain?mentioning
confidence: 99%
“…One potent example is osteoarthritis, which increases in incidence with age but has greater prevalence and severity in women than men across all ages (Boyan et al, 2012, Boyan et al, 2013). Strength and endurance training that rely on fatiguing exercise can be beneficial to treatment and offset pain, however, whether there are sex differences in the response to different exercise regimes is not known (Golightly et al, 2012). The assumption that rehabilitation based on fatiguing exercise at relative intensities after injury or neuromuscular disorder should be similar for men and women is inappropriate, until it is otherwise known.…”
Section: Relevance To Clinical Populations Training and Rehabilitationmentioning
confidence: 99%
“…Physical activity (PA) improves pain and physical function for people with arthritis (35), and a lack of PA is linked with the premature development of chronic diseases (6). The importance of PA for better health and weight management is a well-known public health message (7), yet less than 10% of adults in the United States achieve the 2008 US Department of Health and Human Services PA guidelines (≥150 min/wk of moderate PA or ≥75 min/wk of vigorous PA, or equivalent combination of the 2) (8), and most people with arthritis do not achieve these recommended PA levels (9,10).…”
Section: Introductionmentioning
confidence: 99%